Importance of A-loop complementarity with tRNAHis anticodon for continued selection of tRNAHis as the HIV reverse transcription primer - Morrow Casey D; Xu Wenqin; Ni Na (Virology Journal, 2007)
Abstract Background Human immunodeficiency virus (HIV-1) preferentially selects tRNALys,3 as the primer for reverse transcription. HIV-1 can be forced to select alternative tRNAs through mutation in the primer-binding site (PBS) and a region upstream of the PBS designated as the A-loop. Alteration of the PBS and A-loop to be complementary to the 3' terminal nucleotides and anticodon of tRNAHis results in HIV-1 that can stably utilize this tRNA for replication. Results In the current study, we have investigated the effect that mutations within the A-loop have on the stability of HIV-1 with a PBS complementary to tRNAHis. For these studies, we have altered the A-loop to be complementary to tRNAMet, tRNAGln, tRNAIle, tRNAThr and tRNASer. All substitutions of the A-loops with the PBS complementary to tRNAHis resulted in a reduction of infectious virus obtained following transfection of proviral genomes in the 293T cells. Virus replication in SupT1 cells was also impaired as a result of the alteration of the A-loop. Viruses with the A-loop complementary to tRNALys,3 and tRNASer reverted to utilize tRNALys,3 following in vitro replication. In contrast, viruses with the A-loop complementary to the other tRNAs remained stable and continued to use tRNAHis. RNA modeling of the stem-loop structure revealed that nucleotides were displayed on the loop region that could potentially interact with the anticodon of tRNAHis. To further explore the effects of the A-loop mutations on virus replication, the A-loops complementary to tRNASer or tRNAHis were cloned into the wild type genome with the PBS complementary to tRNALys,3. Transfection of proviral genomes which contained the wild type PBS and A-loops complementary to tRNASer or tRNAHis into 293 T cells did not impact on the production of viruses as measured by p24 antigen ELISA. However, viruses with the A-loop complementary to tRNAHis had greatly reduced infectivity and replicated poorly in SupT1 compared to the wild type or viruses with the A-loop complementary to tRNASer. Conclusion These studies demonstrate that complementarity of A-loop region with the anticodon of tRNAHis has a pronounced effect on the capacity of HIV-1 to utilize tRNAHis as the primer for reverse transcription. Complementarity between A-loop and anticodon of the tRNA then is important for the selection of the tRNA primer used for reverse transcription.